Testing the Newcomb-Benford Law: experimental evidence. Issue 21 (15th December 2019) - Hassler, Uwe; Hosseinkouchack, Mehdi
ABSTRACT: The (Newcomb-)Benford Law has been widely used to detect fraud in data from accounting and finance, or in economic, survey and scientific data. Many empirical studies rely on the outcomes of two particular statistical tests. Our power investigation shows that these tests are weak in terms of power under specific fraudulent pattern. Much more powerful criteria are identified, and in particular, a simple, one-sided mean test is recommended.